Natural image restoration based on multi-scale group sparsity residual constraints - Ning, Wan; Sun, Dong; Gao, Qingwei; Lu, Yixiang; Zhu, De (Frontiers in Neuroscience, 2023)
The Group Sparse Representation (GSR) model shows excellent potential in various image restoration tasks. In this paper, we propose a novel Multi-Scale Group Sparse Residual Constraint Model (MS-GSRC) which can be applied to various inverse problems, including denoising, inpainting, compressed sensing(CS), etc. Our new method involves three steps: (1) finding similar patches with an overlapping scheme for the input degraded image using a multi-scale strategy, (2) performing a group sparse coding on these patches with low-rank constraints to get an initial representation vector, (3) under the Bayesian maximum a posteriori(MAP) restoration framework, we adopt an alternating minimization scheme to solve the corresponding equation and reconstruct the target image finally. Simulation experiments demonstrate that our proposed model outperforms in terms of both objective image quality and subjective visual quality compared to several state-of-the-art methods.